The experience of men whose partners are hospitalized for high-risk pregnancies - a phenomenological study - Noftall, Alice, 1955- (St. John's, NF : [s.n.], 2000)
Thesis (M.N.)--Memorial University of Newfoundland, School of Nursing, 2000. Nursing Bibliography: leaves 109-116.